2019
DOI: 10.3758/s13414-019-01695-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of context and expertise on attention: is attention shifted by information in medical images?

Abstract: Radiologists make critical decisions based on searching and interpreting medical images. The probability of a lung nodule differs across anatomical regions within the chest, raising the possibility that radiologists might have a prior expectation that creates an attentional bias. The development of expertise is also thought to cause “tuning” to relevant features, allowing radiologists to become faster and more accurate at detecting potential masses within their domain of expertise. Here, we tested both radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 44 publications
(67 reference statements)
4
31
0
Order By: Relevance
“…Although years of experience is often regarded as an indicator of expertise, this factor is difficult to measure as it represents overlapping variables that incorporate a number of dimensions which increase the variability in performance (Heilman and Stopeck 1985 ), such as individual differences. Studies in radiology have shown that experience bares little relationship with visual tasks such as spatial attention cueing (Carrigan et al 2019a , 2019b ), visual search strategies (Williams and Drew 2019 ), or nodule detection (Sunday et al 2018 ). Medical image perception researchers are finding that it is difficult to tease apart experience and learned strategies (Williams and Drew 2019 ), suggesting that there are other several other factors contributing to the development of expertise.…”
Section: Experiments 3: Diagnostic Performance Of Echocardiographers Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Although years of experience is often regarded as an indicator of expertise, this factor is difficult to measure as it represents overlapping variables that incorporate a number of dimensions which increase the variability in performance (Heilman and Stopeck 1985 ), such as individual differences. Studies in radiology have shown that experience bares little relationship with visual tasks such as spatial attention cueing (Carrigan et al 2019a , 2019b ), visual search strategies (Williams and Drew 2019 ), or nodule detection (Sunday et al 2018 ). Medical image perception researchers are finding that it is difficult to tease apart experience and learned strategies (Williams and Drew 2019 ), suggesting that there are other several other factors contributing to the development of expertise.…”
Section: Experiments 3: Diagnostic Performance Of Echocardiographers Vmentioning
confidence: 99%
“…Those with expertise in a particular domain can also rapidly extract a large amount of relevant information from features in the environment (Abernethy 1987 ; Kundel and Nodine 1975 ; Nodine and Krupinski 1998 ), where a superior ability develops to encode large scale visual patterns (Drew et al 2013 ). In the context of medical imaging, radiologists, but not naïve participants, can detect abnormalities at above what is expected by chance after viewing the images for < 1 s (Brennan et al 2018 ; Carrigan et al 2019a ; Donovan and Litchfield 2013 ; Evans et al 2013 ; Evans et al 2016 ; Kundel and Nodine 1975 ; Kundel et al 2008 ). Eye-tracking studies indicate that expert radiologists fixate faster and more accurately on an abnormality in mammographic images than less-experienced radiologists and use fewer eye movements to do so (Kundel and La Follette Jr 1972 ; Kundel and Nodine 1975 ).…”
Section: Introductionmentioning
confidence: 99%
“…Decades of research in medical perceptual domains have demonstrated a domain specific, perceptual superiority for experts compared with novices. For example, radiologists adopt an efficient search strategy when interpreting medical images (e.g., Kundel & Nodine, 1975), and they can detect a lung nodule following a brief presentation of a chest X‐ray, whereas naïve participants cannot (Carrigan et al, 2019). Similar findings have been shown in the non‐medical domain with car experts (e.g., Curby et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the medical imaging domain, radiology experts have the remarkable capacity to rapidly and accurately detect abnormalities in chest X-Rays (Carrigan, Curby, Moerel, & Rich, 2019;Kundel & Nodine, 1975) and mammograms (Brennan et al, 2018;Carrigan, Wardle, & Rich, 2018;Evans, Georgian-Smith, Tambouret, Birdwell, & Wolfe, 2013). Nodine and Krupinski (1998) and Charness, Krampe, and Mayr (1996) proposed that, with exposure and deliberate practice, a perceptual fine-tuning develops for relevant features and patterns.…”
mentioning
confidence: 99%
“…Medical images contain a high variability of physical properties and image artifacts, which altogether lead to distracted visual attention [47]. Moreover, the semantic context of medical images may mask the effect of the physical properties of the display and visual stimulus [25].…”
Section: Visual Stimulimentioning
confidence: 99%